Speaking truths : young adults, identity, and spoken word activism - Chepp, Valerie (Rutgers University Press, 2022)
"The twenty-first century is already riddled with protests demanding social justice, and in every instance, young people are leading the charge. But in addition to protesters who take to the streets with handmade placards are young adults who engage in less obvious change-making tactics. In Speaking Truths, sociologist Valerie Chepp goes behind-the-scenes to uncover how spoken word poetry-and young people's participation in it-contributes to a broader understanding of contemporary social justice activism, including this generation's attention to the political importance of identity, well-being, and love. Drawing upon detailed observations and in-depth interviews, Chepp tells the story of a diverse group of young adults from Washington, D.C. who use spoken word to create a more just and equitable world. Outlining the contours of this approach, she interrogates spoken word activism's emphasis on personal storytelling and "truth," the strategic uses of aesthetics and emotions to politically engage across difference, and the significance of healing in sustainable movements for change. Weaving together their poetry and personally told stories, Chepp shows how poets tap into the beautiful, emotional, personal, and therapeutic features of spoken word to empathically connect with others, advance intersectional and systemic analyses of inequality, and make social justice messages relatable across a diverse public. By creating allies and forging connections based on friendship, professional commitments, lived experiences, emotions, artistic kinship, and political views, this activist approach is highly integrated into the everyday lives of its practitioners, online and face-to-face. Chepp argues that spoken word activism is a product of, and a call to action against, the neoliberal era in which poets have come of age, characterized by widening structural inequalities and increasing economic and social vulnerability. She illustrates how this deeply personal and intimate activist approach borrows from, builds upon, and diverges from previous social movement paradigms. Spotlighting the complexity and mutual influence of modern-day activism and the world in which it unfolds, Speaking Truths contributes to our understanding of contemporary social change-making and how neoliberalism has shaped this political generation's experiences with social injustice"--